A Novel Microviridae Phage (CLasMV1) From “Candidatus Liberibacter asiaticus” - Zhang, Ling; Li, Ziyi; Bao, Minli; Li, Tao; Fang, Fang; Zheng, Yongqin; Liu, Yaoxin; Xu, Meirong; Chen, Jianchi; Deng, Xiaoling; Zheng, Zheng (Frontiers in Microbiology, 2021)
“Candidatus Liberibacter asiaticus” (CLas) is an unculturable phloem-limited α-proteobacterium associated with citrus Huanglongbing (HLB, yellow shoot disease) HLB is currently threatening citrus production worldwide. Understanding the CLas biology is critical for HLB management. In this study, a novel single-stranded DNA (ssDNA) phage, CLasMV1, was identified in a CLas strain GDHZ11 from Guangdong Province of China through a metagenomic analysis. The CLasMV1 phage had a circular genome of 8,869 bp with eight open reading frames (ORFs). While six ORFs remain uncharacterized, ORF6 encoded a replication initiation protein (RIP) and ORF8 encoded a major capsid protein (MCP). Based on BLASTp search against GenBank database, amino acid sequences of both MCP and RIP shared similarities (Coverage > 50% and identity > 25%) to those of phages in Microviridae, a ssDNA phage family. Phylogenetic analysis revealed that CLasMV1 MCP and RIP sequence was clustered with genes from CLas and “Ca. L. solanacearum” (CLso) genomes and formed a unique phylogenetic lineage, designated as a new Subfamily Libervirinae, distinct to other members in Microviridae family. No complete integration form but partial sequence ( 1.9 kb) of CLasMV1 was found in the chromosome of strain GDHZ11. Reads-mapping analyses on additional 15 HiSeq data sets of CLas strains showed that eight strains harbored complete CLasMV1 sequence with variations in single nucleotide polymorphisms (SNPs) and small sequence insertions/deletions (In/Dels). PCR tests using CLasMV1-specific primer sets detected CLasMV1 in 577 out of 1,006 CLas strains (57%) from southern China. This is the first report of Microviridae phage associated with CLas, which expands our understanding of phage diversity in CLas and facilitates current research in HLB.